The role of autophagy in initiation, progression, TME modification, diagnosis, and treatment of esophageal cancers. (July 2022) - Zhou, Suna; Sun, Xuefeng; Jin, Zhicheng; Yang, Haihua; Ye, Wenguang
Abstract: Autophagy is a highly conserved metabolic process with a cytoprotective function. Autophagy is involved in cancer, infection, immunity, and inflammation and may be a potential therapeutic target. Increasing evidence has revealed that autophagy has primary implications for esophageal cancer, including its initiation, progression, tumor microenvironment (TME) modification, diagnosis, and treatment. Notably, autophagy displayed excellent application potential in radiotherapy combined with immunotherapy. Radiotherapy combined with immunotherapy is a new potential therapeutic strategy for cancers, including esophageal cancer. Autophagy modulators can work as adjuvant enhancers in radiotherapy or immunotherapy of cancers. This review highlights the most recent data related to the role of autophagy regulation in esophageal cancer. Highlights: Autophagy acts as a cytoprotective response in virtually all human normal and malignant cells. Autophagy participates fully in initiation, progression, and TME modification of esophageal cancer. Autophagy-related markers show diagnostic and prognostic power in esophageal cancer. Autophagy modulators can be applied as adjuvant enhancers in anti-tumor therapy including radiotherapy or immunotherapy.